2012
DOI: 10.1038/bmt.2012.257
|View full text |Cite
|
Sign up to set email alerts
|

In a high-dose melphalan setting, palifermin compared with placebo had no effect on oral mucositis or related patient’s burden

Abstract: on behalf of the CLWP of the EBMT This randomized-controlled trial studied the efficacy of palifermin in a chemotherapy-only, high-dose Melphalan (HDM) transplant setting, to reduce oral mucositis (OM) and its sequelae measured by patient-reported outcomes (PRO) and medical resource use. Palifermin, relative to placebo was given either pre-/post-HDM or pre-HDM in patients with multiple myeloma (MM) undergoing auto-SCT at 39 European centers. Oral cavity assessment (WHO) and PRO questionnaires (oral mucositis d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 20 publications
2
37
0
2
Order By: Relevance
“…Palifermin administered pre-and post-HDM was studied in a randomized fashion with no beneficial effect on mucositis incidence and on fever. 63 Other studies, however, found a positive impact of palifermin on infection rate after BEAM-like conditionings or after TBI. [64][65][66] Furthermore, some studies suggested that, though palifermin was not effective in reducing overall infection rate (mostly central venous catheter related), its use may reduce 'severe' infections such as those due to Gramnegative pathogens or accompanied by focal pneumonia.…”
Section: Hdc Administration Hpc Infusionmentioning
confidence: 98%
“…Palifermin administered pre-and post-HDM was studied in a randomized fashion with no beneficial effect on mucositis incidence and on fever. 63 Other studies, however, found a positive impact of palifermin on infection rate after BEAM-like conditionings or after TBI. [64][65][66] Furthermore, some studies suggested that, though palifermin was not effective in reducing overall infection rate (mostly central venous catheter related), its use may reduce 'severe' infections such as those due to Gramnegative pathogens or accompanied by focal pneumonia.…”
Section: Hdc Administration Hpc Infusionmentioning
confidence: 98%
“…Şiddetli oral mukozit ve süresi yüksek doz kemoterapi alma ile önemli oranda ilişkilidir. (12) HKHN yapılan hastalarla yürütülen çalışmalara bakıldığında temel ağız bakımı, oral kriyoterapi veya düşük-düzeyli lazer tedavisi oral mukoziti önleme ve tedavisinde etkin yaklaşımlar arasındadır. (13) …”
Section: öZunclassified
“…Şiddetli oral mukoziti önlemeye yönelik HKHN uygulanan hastalarda Food and Drug Administration (FDA) tarafından onaylanan ilk ajandır. (31) Blijlevens ve arkadaşları (12) paliferminin etkisini yüksek doz Melphalan alan otolog HKHN hastalarında oral mukozit şiddetini değerlendirmek üzere yaptıkları randomize kontrollü çalışmada 277 hastayı dahil etmişlerdir. Plasebo (n=57), preyüksek doz melphalan (YDM) alan hasta (n=107) ve pre/post yüksek doz melphalan hasta (n=107) grubu olmak üzere 3 grup oluşturulmuştur.…”
Section: Diğer Uygulamalarunclassified
“…The importance of conditioning is suggested, in fact, by studies from Herbers et al who reported that palifermin administration in patients treated using a BEAM conditioning schedule leads to a reduction in the rate of some infections such as 'fever of unknown origin' (FUO), 9 while the same group did not find this effect in patients treated with high-dose melphalan (HD-PAM). 10 In a previous work we indeed found that conditioning significantly interacts with the effects of palifermin and that this agent is able to reduce the rate of severe mucositis only after conditioning based on BEAM or on BU/Thiothepa treatment but not after 'HD-PAM' conditioning. 11 Now we present an analysis in which we have assessed the effect of palifermin on infection risk according to the conditioning regimen used.…”
Section: Introductionmentioning
confidence: 99%